Influence of Dietary Incorporation of Vegetable Oils and Microalgae on Laying Hens Egg Yolk Fatty Acids Profile and Health Lipid Indices - Gordana Kralik; Zlata Kralik; Manuela Košević; Igor Kralik; Kristina Gvozdanović (Poljoprivreda)
Table eggs are a good source of nutrients. The nutritional properties of eggs are influenced by the composition of laying hens’ feed mixtures. An important compo-nent in the feed mixtures are the oils, which, in addition to their energy value, are also important for the absorption of liposoluble vitamins. Oils differ in the content of fatty acids, which play a significant role in metabolism and health maintenance. The lipid indices, such as the atherogenic (AI), thrombogenic (TI), and hypo/hypercho-lesterolemic fatty-acid ratio index (HH), are used when evaluating the lipid-quality indicators in eggs. This study aimed to produce the eggs enriched with the n-3 PUFA and to determine which feeding treatment yields the eggs with the most favorable lipid quality. The three groups of layers (treatments A, B, and C) were used in the experiment, which were fed with the mixtures of a modified composition considering the oils and microalgae used. The mixtures were balanced at the level of 17% crude protein and 12.10 MJ/kg ME. The produced eggs were used for an analysis of fatty-acid content (SFA, MUFA, n-6 PUFA, and n-3 PUFA), on the basis of which the lipid indices were calculated. The research results of eggs from the A, B, and C feeding treatments showed that the AIs were 0.485, 0.476, and 0.453; the TIs were 0.802, 0.681, and 0.653, and the HH indices amounted to 2.976, 2.983, and 3.068. The activi-ties of the Λ5- and Λ6 desaturases in the synthesis of the n-6 PUFA and the n-3 PUFA in eggs differed between the feeding treatments. The influence of a composition of feed mixtures in the laying hens’ diet on the quality of lipid indices was determined, and the eggs from the treatment C had the most favorable health-lipid indices.